Description of the female terminalia of twelve species of Proconiini and a key to genera from Argentina (Insecta: Hemiptera: Cicadellidae) - Dellapé, Gimena (2016)
The female terminalia of 12 sharpshooter species are described and illustrated: Aulacizes basalis, A. conspersa, A. insistans, A. obsoleta, A. quadripunctata, Cicciana latreillei, Pseudometopia amblardii, Stictoscarta sulcicollis, Tretogonia bergi, T. cribata, T. dentalis, and T. notatifrons. A key to the identification of the Argentinean Proconiini genera including male and female characters is provided.